2022
DOI: 10.24925/turjaf.v10i12.2545-2553.5556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pink Rock Rose Extract with or Without Ascorbic Acid and Sodium Ascorbate for the Preservation of Ready-to-Eat Frankfurter Type Sausages

Abstract: This study aimed to determine the effect of pink rock rose extract (PRR) with or without ascorbic acid and sodium ascorbate for improving the shelf life of sausages. Analyzed parameters were DPPH radical scavenging capacity of PRR extract; total aerobic count, thiobarbituric acid reactive substance, heme iron, pH, water activity, proximate composition, and color values of MAP packaged sausages for 12 weeks at 4 °C. Treatments: (1) Control (0.02% ascorbic acid and 0.05% sodium ascorbate – AA-SA), (2) electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this study, the sensory properties of T2, which were located on the opposite dimension of overall acceptability, may have a negative effect on the quality of pork sausage, while those of T3 were related to a positive effect on the quality of pork sausage. Additionally, studies have shown that adding ascorbic acid to natural extracts increases the antibacterial effect ( Gedikoğlu et al, 2022 ). However, no significant effect of ascorbic acid was observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the sensory properties of T2, which were located on the opposite dimension of overall acceptability, may have a negative effect on the quality of pork sausage, while those of T3 were related to a positive effect on the quality of pork sausage. Additionally, studies have shown that adding ascorbic acid to natural extracts increases the antibacterial effect ( Gedikoğlu et al, 2022 ). However, no significant effect of ascorbic acid was observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…They can exhibit their antioxidant activity by the mechanism of donating electrons or protons to scavenge free radicals, to chelate metal ions, or to inhibit enzymes responsible for radical generation (Irigoiti et al, 2021). In previous studies, IC50 values of some of the pure antioxidant compounds have been reported as follows: gallic acid (3.53 µg/mL), quercetin (6.55 µg/mL), rutin (9.44 µg/mL) (Singh et al, 2018), and ascorbic acid (5.59 µg/mL) (Gedikoğlu et al, 2022). In this study, C. creticus extracts demonstrated strong radical scavenging activity for the DPPH radical.…”
Section: Total Phenolic and Flavonoid Content And Antioxidant Activit...mentioning
confidence: 99%